Understanding the Learning Models Design for Indonesian Teacher - Ira Irviana Irvy (International Journal of Asian Education, 2020)
This paper aims to provide an understanding of how a teacher designs a learning model. Many writings discuss learning models, but they cannot be applied in a learning process. This paper is expected to provide experience for teachers in planning and developing learning through development models. Planning is essential because it is a managerial process in determining what to do and how to do it, and in it, the goals that will be achieved and work programs are developed to achieve goals. Therefore, learning planning is a decision-making process as a result of reasoning about specific learning goals and objectives, namely changes in behavior and a series of activities that must be carried out to achieve these goals by utilizing all existing potential and learning resources. In integrating a study, one can see the types of material that have a relationship with one another, for example, learning characters and morals, which, if studied, will lead to one point, namely a good personality. More generally, if the integration of fields of study, such as the field of religious education and character, which is integrated with the field of civic education, there are moral and character values. The material in learning to integrated several types of development models can be selected, including ASSURE, ADDIE, Jerold E. Kamp, et al., Dick & Carey, and Gerlach & Ely.